2016
DOI: 10.1214/15-aos1364
|View full text |Cite
|
Sign up to set email alerts
|

Projected principal component analysis in factor models

Abstract: This paper introduces a Projected Principal Component Analysis (Projected-PCA), which employees principal component analysis to the projected (smoothed) data matrix onto a given linear space spanned by covariates. When it applies to high-dimensional factor analysis, the projection removes noise components. We show that the unobserved latent factors can be more accurately estimated than the conventional PCA if the projection is genuine, or more precisely, when the factor loading matrices are related to the proj… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 129 publications
(52 citation statements)
references
References 43 publications
0
51
0
1
Order By: Relevance
“…On the other hand, if the dimension is much larger than the sample size, we offset the dimensionality by assuming increased signals or sample size, without additional sparse eigenvector assumption as in sparse PCA regime. In particular, as shown in (1.1), the strong (or pervasive) factors considered in financial applications corresponds to γ j = 0 with the leading eigenvalues λ j ≍ p ; see for example Stock and Watson (2002); Bai (2003); Bai and Ng (2002); Fan, Liao and Mincheva (2013); Fan, Liao and Wang (2016). The weak or semi-strong factors considered by De Mol, Giannone and Reichlin (2008) and Onatski (2012) also imply bounded p /( n λ 1 ), with p/n bounded and λ j ≍ p θ for some θ ∈ [0, 1).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, if the dimension is much larger than the sample size, we offset the dimensionality by assuming increased signals or sample size, without additional sparse eigenvector assumption as in sparse PCA regime. In particular, as shown in (1.1), the strong (or pervasive) factors considered in financial applications corresponds to γ j = 0 with the leading eigenvalues λ j ≍ p ; see for example Stock and Watson (2002); Bai (2003); Bai and Ng (2002); Fan, Liao and Mincheva (2013); Fan, Liao and Wang (2016). The weak or semi-strong factors considered by De Mol, Giannone and Reichlin (2008) and Onatski (2012) also imply bounded p /( n λ 1 ), with p/n bounded and λ j ≍ p θ for some θ ∈ [0, 1).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the matrix F captures information in U that cannot be explained by Y. We note that very recently Fan et al [13] proposed a projected principal component analysis (PCA) method that generalizes the second equation of (1) to a semi-parametric model.…”
Section: Introductionmentioning
confidence: 99%
“…Additional works on semi-parametric factor models include, e.g., Park et al (2009) and Song et al (2014). Fan et al (2016b) recognized that the above semi-parametric model (7.1) might be restrictive for applications, as we do not expect that the covariates capture completely the factor loadings. They extend the model to the following more flexible semi-parametric mixed effect model:…”
Section: Motivationsmentioning
confidence: 99%
“…To deal with the curse of dimensionality, we assume g k (·) to be additive: g k (X i ) = d l=1 g kl (X il ), with d = dim(X i ). Applying the projected PCA on to the semi-parametric factor model, Fan et al (2016b) showed that as p, J → ∞, T may either grow or stay constant,…”
Section: Semi-parametric Factor Modelsmentioning
confidence: 99%
See 1 more Smart Citation